Achieving a strong second harmonic generation response and a wide band gap in a Hg-based material. Issue 16 (29th June 2022) - Zhang, Yujie; Wu, Hongping; Hu, Zhanggui; Wang, Jiyang; Wu, Yicheng; Yu, Hongwei
Abstract : The property-oriented structural design strategy is employed in Hg-based chalcogenide to synthesize a new IR NLO crystal, [Ba4 Cl2 ][HgGa4 S10 ], which exhibits well-balanced NLO properties, including large SHG response and wide band gap. Abstract : A new Hg-based infrared nonlinear optical (IR NLO) crystal, [Ba4 Cl2 ][HgGa4 S10 ], was synthesized based on a property-oriented structural design strategy. It crystallizes in the noncentrosymmetric tetragonal space group ( I 4̄) and consists of a 3D [HgGa4 S10 ] 6− anionic moiety formed by corner-sharing tetrahedral HgS4 and supertetrahedral Ga4 S10 clusters, as well as a 3D [Ba4 Cl2 ] 6+ cation network. The physical property measurements show that it can exhibit well-balanced NLO performances, including a large second-harmonic generation (SHG) response (1.5 × AgGaS2 ), wide band gap (2.95 eV), and high laser damage threshold (∼15 × AgGaS2 ). First-principles calculations indicate that the large SHG response of [Ba4 Cl2 ][HgGa4 S10 ] mainly originates from the strong covalent HgS4 and GaS4 tetrahedra and the ionic bonding [Ba4 Cl2 ] 6+ guest network contributes to the wide band gap of [Ba4 Cl2 ][HgGa4 S10 ].